Isolation and Antimicrobial Susceptibility Profile of Citrobacter Species from Small Ruminants and Water Sources - Ejeh, Enenche Francis; Lekko, Yusuf Madaki; Lawan, Fatima Adamu; Ndahi, Juliana James; Abdullahi, Adama Musa (Journal of Applied Veterinary Science And Technology, 2025)
Background: Citrobacter species are gram negative, enteric bacilli that are mostly found in water, soil, food, and intestine of animals and humans causing wide range of infections. Purpose: It will provide critical insights that can improve the diagnosis, treatment, and management of infections caused by Citrobacter species, thereby enhancing the overall health of small ruminants. Method: A cross-sectional study using stratified random sampling method was used. A total of 120 samples were analyzed, consisting of 116 from small ruminants and 4 from water. Samples were cultured on selective media and Mac Conkey Agar. Antimicrobial sensitivity testing was done for Citrobacter species using Kirby-Bauer disc diffusion method and are classify as susceptible, intermediate, or resistant for each antimicrobial agent. Results: A total of 23 isolates (19.2%) were identified as Citrobacter species, while 97 isolates (80.8%) belonged to other members of the Enterobacteriaceae family. Citrobacter species showed a 100% prevalence in water samples, compared to 16.4% in small ruminants. Statistical analysis demonstrated a significant association between Citrobacter occurrence and factors including sample source (p = 0.000), age (p = 0.000), and breed (p = 0.002). Antimicrobial susceptibility testing revealed that Citrobacter portucalensis isolates exhibited complete resistance (100%) to cefotaxime and ceftriaxone, with similarly high resistance levels to amoxicillin/clavulanic acid (94.7%), pefloxacin (84.2%), cephalexin (84.2%), and trimethoprim/sulfamethoxazole (89.5%). Ofloxacin showed the greatest level of susceptibility (73.7%), although resistance was still observed in 21.0% of the isolates.. Conclusion:  The detection of Citrobacter species in both animals and water underscores the need for effective therapeutic choices and environmental control to reduce antimicrobial resistance.